Navigating uncertainty in patient care: a closer look at emergency medicine residents in Brazil - Boemeke, Gabriela; Barbosa, Larissa A. O.; Menezes, Rodrigo C.; Quintanilha, Luiz F.; Avena, Katia M.; Andrade, Bruno B. (Frontiers in Medicine, 2025)
BackgroundIn emergency care, inexperience and case complexity can generate uncertainty and stress among physicians, impairing decision-making and impacting patients and the healthcare system. Despite its relevance, little is known about uncertainty among Emergency Medicine residents (EMRs).AimTo investigate decision-making uncertainty among EMRs, identifying the most affected dimensions and the influence of sociodemographic and academic profiles.MethodsThis cross-sectional study included EMRs in Brazil, regardless of residency year. Data were collected via snowball sampling using an anonymous electronic form distributed through virtual groups and email. Information on sociodemographic/academic characteristics, as well as the Physicians’ Reactions to Uncertainty (PRU) questionnaire, was obtained.ResultsA total of 124 EMRs participated (median age 28 years; 52% female). The majority of the participants were first-year residents (49%), with no prior residency experience (92%) or other healthcare degrees (94%). The Southeast region was most represented (38%). The median PRU score was 49.0 (IQR: 41.0–57.0), with the highest scores observed in anxiety due to uncertainty (21.0) and reluctance to disclose uncertainty to patients (13.0). Cluster analysis identified three groups: high (43%), moderate (35%), and low (22%) uncertainty. Male and third-year residents had significantly lower total PRU scores, especially in anxiety (p = 0.023 and p = 0.017). Previous healthcare training or residency did not significantly affect uncertainty levels.ConclusionEMRs show substantial uncertainty in decision-making, particularly in anxiety and reluctance to disclose uncertainty to patients. First-year residents and those without prior healthcare training or residency are more affected. Male and more experienced residents report lower uncertainty, especially regarding anxiety. These findings suggest that targeted interventions—such as enhanced training and structured support—could help EMRs manage uncertainty, improving both decision-making and well-being in emergency settings.